Diagnosis of the anatomic preconditions of intermittent testicular torsion - D. E. Sablin; V. V. Sizonov; I. M. Kagantsov; V. B. Shamik; Yu. V. Lukash (Вестник урологии)
Introduction. In a series of studies, patients with intermittent testicular torsion (ITT) have a 29% to 50% chance of gonad loss. The «bell clapper» type testicular fixation abnormality is a predisposing factor for TT. In cases of ITT, episodes of hemiscrotal pain attack are not a sufficient reason to scrotal revision, which makes it important to develop imaging techniques to document the presence of anatomical preconditions for ITT.Objective. To find a methodology beneficial in solving the problem of documenting the anatomical preconditions for ITT.Materials & methods. To diagnose anatomical preconditions of ITT, we have developed a method of ultrasound. Ultrasound can be used to prove the presence of a “bell clapper» deformity by visualizing the spermatic cord proximal to the testis surrounded by fluid. Fix the testis with a slight traction in a caudal direction while moving the fluid inside the sheaths upward. Place the transducer over the spermatic cord in a horizontal position. The fluid is displaced abnormally high along the spermatic cord within the peritoneal vaginal sheath and surrounds the spermatic cord on all sides, allowing good visualization of the spermatic cord above the testis within the testicular sheaths. If we continue with the bell analogy, the resulting ultrasound picture can be called «bell clapper rod» symptom. A patient with an ultrasound-derived «bell clapper rod» symptom can be diagnosed with a testicular fixation anomaly that creates anatomic conditions for intermittent testicular torsion. The ultrasound arguments obtained allow us to confidently form indications for testicular fixation.Results. Eight patients were examined according to the described method, all of them showed the symptom of ‘bell clapper rod’, and testicular fixation was recommended. The average age of the patients was 12.4 years. The average time after scrotal pain resolution was 8 hours (from 1 to 18 hours). All eight patients had intraoperative verification of abnormal testicular fixation of the ‘bell clapper rod’.Conclusion. A patient with the acute hemiscrotal pain and then its spontaneous disappearance with the ultrasound-derived «bell clapper rod» symptom can be diagnosed with a testicular fixation anomaly that creates anatomic conditions for ITT. Preoperative diagnosis based on ultrasound combined with clinical data transforms the ITT from a diagnosis of exclusion to a diagnosis based on proven anatomical preconditions for testicular torsion. The ultrasound arguments obtained allow us to confidently form indications for testicular fixation.